Multiparametric MR Evaluation of the Photoperiodic Regulation of Hypothalamic Structures in Sheep - Just, Nathalie; Chevillard, Pierre Marie; Batailler, Martine; Dubois, Jean-Philippe; Vaudin, Pascal; Pillon, Delphine; Migaud, Martine (Neuroscience, 2023)
[Display omitted] •BOLD responses were sensitive to photoperiod over the whole ewe brain.•Hypothalamic negative BOLD coincided with early short days.•Hypothalamic rCBV, tNAA and Glx concentrations changed significantly.•These photoperiodic changes promoted neuronal proliferation and differentiation.•Sheep is a promising model for the assessment of natural neurogenesis. Most organisms on earth, humans included, have developed strategies to cope with environmental day-night and seasonal cycles to survive. For most of them, their physiological and behavioral functions, including the reproductive function, are synchronized with the annual changes of day length, to ensure winter survival and subsequent reproductive success in the following spring. Sheep are sensitive to photoperiod, which also regulates natural adult neurogenesis in their hypothalamus. We postulate that the ovine model represents a good alternative to study the functional and metabolic changes occurring in response to photoperiodic changes in hypothalamic structures of the brain. Here, the impact of the photoperiod on the neurovascular coupling and the metabolism of the hypothalamic structures was investigated at 3T using BOLD fMRI, perfusion-MRI and proton magnetic resonance spectroscopy (1H-MRS). A longitudinal study involving 8 ewes was conducted during long days (LD) and short days (SD) revealing significant BOLD, rCBV and metabolic changes in hypothalamic structures of the ewe brain between LD and SD. More specifically, the transition between LD and SD revealed negative BOLD responses to hypercapnia at the beginning of SD period followed by significant increases in BOLD, rCBV, Glx and tNAA concentrations towards the end of the SD period. These observations suggest longitudinal mechanisms promoting the proliferation and differentiation of neural stem cells within the hypothalamic niche of breeding ewes. We conclude that multiparametric MRI studies including 1H-MRS could be promising non-invasive translational techniques to investigate the existence of natural adult neurogenesis in-vivo in gyrencephalic brains.